Control por PLC de la conductividad eléctrica en un sistema de generación de la solución para un cultivo hidropónico (2020)
A module for the generation of the nutrient solution for a hydroponic culture, also an electric conductivity probe was charecterized, this probe measures the nutrient concentration in the solution and sends that sgnal to a PLC to control that variable in the solution.